Effect of Basel III capital requirements on bank lending rates - Mitrová, Martina (2014)
The bachelor thesis studies changes in bank capital requirements brought by new regulatory framework Basel III cross-sectionally in both qualitative and quantitative manner. Theoretical knowledge is applied on utilization of an appropriate accounting model to estimate impact of changes in required capital adequacy on customer bank loan rates. The used sample consists of top bank groups of EU area for year 2013.